Population Study, Length-weight Relationship, Size and Movement of Acrossocheilus Deauratus (euvier & Valenciennes) in Two Malaysian Streams - Ambak, Mohd Azmi; Mohammad Mohsin, Abu Khair (1980)
A survey of the population estimation of'ikan daun' (Acrossocheilus deauratus) on Sungai Batu and Sungai Tua in Selangor, Malaysia was done. A small stretch of 1.5 km each in Sungai Batu and Sungai Tua represented 3,969 and 1,932 'ikan daun' respectively. The length of the fishes varies from 53-115 mm and the length-weight relationship was represented by the formulae: Sungai Batu, Loge W = Log e 0.0006 + 2.2956 Log e L, and Sungai TZ!a, Loge W = Loge 0.0001 + 2.7003 Loge L. Ecological conditions in Sungai Batu were favourable for the 'ikan daun' population. There is no evidence of shoal movements occurring in these two streams but some individual movement did occur.